Obraz zbrodni we współczesnych wybranych reportażach literackich = The image of the crime in chosen modern literary reportage - Kaczmar, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The interest in criminal activity for several years is almost written in a different forms of activity in the framework of massculture. Emphasize on details causes that most of younger viewers stop responding on the gruesome images. What is more they even get used to the view of blood, severed limbs and another gory details. Their sensitivity decreases, and they get interested after the emergence of even more cruel murder. Also popular literature, especially crime story, is full of violence, including the detailed representations of the crime.
Keywords: reportaż polski; literatura kryminalna; paradokument